Implementation of the Rehabilitation and Reconstruction Policy Under Local Regulation No. 8 Of 2013 Following the November 2025 Floods in Medan Barat District, Medan City - Dennis Jesse Siregar; Evi Yunita Kurniaty; Indra Muda (Sean Institute, 2026)
Floods are one of the most common hydrometeorological disasters in Indonesia and have various impacts on people’s lives, infrastructure, the environment, and economic activities. These impacts are not only felt when the disaster occurs but also continue to affect the social and economic conditions of communities in the post-disaster period. Therefore, post-disaster management through rehabilitation and reconstruction is a crucial part of efforts to restore affected areas. The North Sumatra Provincial Government has enacted North Sumatra Provincial Regulation No. 8 of 2013 on Disaster Management as the legal basis for disaster management, including the rehabilitation and reconstruction phases. This study aims to analyze the implementation of rehabilitation and reconstruction policies based on North Sumatra Provincial Regulation No. 8 of 2013 following the November 2025 floods in Medan Barat District, Medan City. This study employed a literature review (library research) using a descriptive qualitative approach. Data were obtained by reviewing various sources, such as laws and regulations, scientific journals, books, government documents, and relevant previous studies. The analysis was conducted using George C. Edward III’s theory of policy implementation, which encompasses communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of rehabilitation and reconstruction policies is influenced by the effectiveness of inter-agency communication, the availability of resources, the commitment of policy implementers, and the clarity of the bureaucratic structure. However, policy implementation still faces obstacles in the form of budget constraints, suboptimal cross-sectoral coordination, and low community participation. Therefore, it is necessary to strengthen institutional capacity, improve coordination among stakeholders, and optimize the disaster management system to achieve more effective and sustainable post-disaster recovery.